Climate change impacts on hydrological regimes under spatially variable human-activity conditions - Liu, Jianwei; Pang, Xiaoteng; Jing, Haihua; Wang, Mingwei; Shen, Longhai; Yan, Xiaohui; Zhang, Qin; Destouni, Georgia (Frontiers in Earth Science, 2025)
The climate change impacts on hydrological conditions may be strongly modulated by the spatial variability of the intensity of human activities within watersheds. Despite growing recognition of climate and anthropogenic influences on hydrological regimes, comprehensive and spatially explicit assessments remain limited, hindering the development of robust watershed management and climate adaptation strategies. In this study, we propose an integrated framework for such analysis and deciphering by combining principal component analysis, hydrological modeling, and a range of variability approach to diagnose and attribute hydrological regime changes. The framework is tested on the case of the Taoer River Basin as a representative watershed system with pronounced human-activity variation along the upstream to downstream direction. Our results show that human activities contribute only 18% to hydrological regime changes in the upstream regions, where anthropogenic influence is relatively low, compared to 49% in the downstream areas with substantially greater human interference. While the upstream areas exhibit more pronounced changes in daily maximum streamflow (78%–79%) and count of low pulses (79%), the downstream areas experience more substantial alterations in monthly average streamflow (84%–99%) and high pulse durations (85%). Overarching the human-activity variability, the climate change impacts increase the risk of flooding, while the human activities exert greater influence in amplifying drought risk. Simulations based on CMIP6 climate projections further indicate a significant increase in the likelihood of upstream flooding. Overall, our findings highlight the necessity of spatially differentiated management and adaptation strategies, tailored to steep human-activity gradients across watershed zones, to effectively address hydrological changes under climate stress.